PENINGKATAN HASIL BELAJAR SISWA KELAS V MELALUI PENERAPAN MEDIA AUDIO VISUAL - Zukfikri Zukfikri; Zulfani Sesmiarni; Rodi; Mira Susanti; Ilva Hendri (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study aims to improve the learning outcomes of fifth grade students through the application of audio-visual media. The background of this study focuses on the low learning outcomes of students caused by conventional teaching methods that are less interesting. Using the experimental method, this study involved two groups of students, namely the experimental group taught using audio-visual media and the control group taught using traditional methods. The results of the data analysis showed that the use of audio-visual media significantly improved students' understanding and learning outcomes. This is evidenced by the increase in the average score in the experimental group compared to the control group. This study concludes that the application of audio-visual media can be an effective alternative in the learning process to improve student learning outcomes. It is hoped that the results of this study can contribute to the development of more innovative teaching methods in elementary schools.